Analisis Framing Logika Media Terkait Pemberitaan Program Kampanye Makan Siang dan Susu Gratis - Situmorang, Ria Theresia (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
This research focuses on news framing analysis by online media in Indonesia related to the source of funds for the free lunch and milk campaign program launched by presidential candidates Prabowo Subianto and Gibran Rakabuming Raka. The focus of this research is to dissect the logic of the media by using framing tools, according to Robert N. Entman. This research uses a qualitative method by using framing tools according to Robert N. Entman and identifying media logic to assess the tendency of journalists and/or media in framing the news about the free lunch and milk campaign program. The data of this study are online news from CNN Indonesia, Kompas, CNBC Indonesia, Tempo, and Detik news sites published on December 20–23, 2023. The results of this study show that each online media has a tendency to frame the news of the free lunch and milk campaign program in media logic with personal and negative identification. This news is heavily influenced by economic aspects because it concerns the source of funds involving tax and non-tax revenues which are considered to be burdensome to the public.